Complications and adverse events of high-intensity focused ultrasound in its application to gynecological field - a systematic review and meta-analysis - Shan-shan Lu; Lei-lei Yang; Wei Yang; Jing Wang; Xia-Lin Zhang; Liu Yang; Yi Wen (International Journal of Hyperthermia)
Objective To analyze and summarize the types, incidence rates and relevant influencing factors of adverse events (AEs) after high-intensity focused ultrasound ablation of gynecological diseases and provide reference and basis for handling such events in clinical practice.Method We searched PubMed, Cochrane Library, Web of Science and Embase databases to retrieve all literature since its establishment until February 2024. We evaluated the quality of included literature and publication bias and conducted a meta-analysis of single group rates for various AEs using Stata 17.0.Results This systematic review finally included 41 articles. We summarized 34 kinds of AEs in 7 aspects and conducted a single group rate meta-analysis and sub-group analysis of 16 kinds of AEs. Among the common AEs of High-Intensity Focused Ultrasound (HIFU), the incidence of lower abdominal pain/pelvic pain is 36.1% (95% CI: 24.3%∼48.8%), vaginal bleeding is 20.6% (95% CI: 13.9%∼28.0%), vaginal discharge is 14.0% (95% CI: 9.6%∼19.1%), myoma discharge is 24% (95% CI: 14.6%∼34.8%), buttock pain is 10.8% (95% CI: 6.0%∼16.5%) and sacral pain is 10% (95% CI: 8.8%∼11.2%). Serious complications include uterine rupture, necrotic tissue obstruction requiring surgical intervention, third degree skin burns and persistent lower limb pain or movement disorders.Conclusion The common AEs after HIFU surgery are mostly mild and controllable, and the incidence of serious complications is extremely low. By reasonable prevention and active intervention, these events can be further reduced, making it a safe and effective treatment method. It is a good choice for patients who crave noninvasive treatment or have other surgical contraindications.